Phototherapeutic keratectomy for recurrent granular dystrophy in postpenetrating keratoplasty eyes - Varsha M Rathi (Indian Journal of Ophthalmology, 2016)
Purpose: The purpose is to assess the clinical and visual outcome after phototherapeutic keratectomy (PTK) procedure in eyes with prior penetrating keratoplasty (PKP) for granular corneal dystrophy (GCD) and the time of performance of repeat PTK for recurrence. Methods: PTK was performed for visually significant recurrence: A reduction in best-corrected visual acuity (BCVA) by >2 lines over BCVA before recurrence was considered as visually significant recurrence. Three eyes had amniotic membrane patch performed with PTK. The main outcome measures were a recurrence of GCD, clinical course, and visual outcome. Intervals between repeat PTK procedures were noted. Results: Six patients (n = 10 eyes; males: 4, mean age 39 ± 13.97 years) underwent PTK. The mean pachymetry before first PTK was 527.1 ± 34 microns. The mean duration between PKP and first PTK was 85.1 months (range: 37–108 months). Two and three PTK procedures were done for seven and five eyes, respectively. Mean duration between first and second and second and third PTK was 62.12 ± 34.41 and 42.8 ± 13.54 months respectively. The average cut depth was 43.66 ± 19.57, 75 ± 43.30 and 39 ± 19.79 microns after the first, second and third PTK procedures, respectively. All eyes had a corneal haze. Pre first PTK mean BCVA was 20/200 and improved significantly after the first two PTK procedures to 20/40 and after the third PTK procedure to 20/32 (P < 0.001). Five eyes had hyperopia. One acute graft rejection was managed successfully at 5 months with medical therapy. Conclusion: Multiple PTK procedures can be performed safely with improved visual acuity in grafts without compromising graft survival.